Renal interstitial fibrosis induced by high-dose mesoporous silica nanoparticles via the NF-κB signaling pathway - Chen X (Dove Medical Press, 2014)
Xi Chen,1,2 Wang Zhouhua,1 Zhou Jie,1 Fu Xinlu,3 Liang Jinqiang,3 Qiu Yuwen,3 Huang Zhiying1,31School of Pharmaceutical Sciences, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Pharmaceutical Department, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 3Center of Laboratory Animals, Sun Yat-sen University, Guangzhou, People’s Republic of China Abstract: Previous studies have indicated that the nephrotoxicity induced by mesoporous silica nanoparticles (MSNs) is closely related to inflammation. Nuclear factor kappa B (NF-κB), a common rapid transcription factor associated with inflammation, plays an important role in the process of many kidney diseases. Acute toxicity assessment with a high-dose exposure is critical for the development of nanoparticle, as a part of standardized procedures for the evaluation of their toxicity. The present study was undertaken to observe the acute toxicity, predict the potential target organs of MSNs injury, and test the hypothesis that the NF-κB pathway plays a role in mediating the acute kidney injury and renal interstitial fibrosis in mice induced by MSNs. Balb/c mice were intraperitoneally injected with MSNs at concentrations of 150, 300, or 600 mg/kg. All of the animals were euthanized 2 and 12 days after exposure, and the blood and kidney tissues were collected for further studies. In vitro, the cytotoxicity, fibrosis markers, and NF-κB pathway were measured in a normal rat kidney cell line (NRK-52E). Acute kidney injury was induced by MSNs in mice after 2 days, some renal tubules regenerated and renal interstitial fibrosis was also observed. The expression of fibrosis markers and the nuclear translocation of NF-κB p65 in the kidney homogenates increased after exposure to MSNs. The in vitro study showed that MSNs cause cytotoxicity in NRK-52E cells and increased the expression of fibrosis markers. In addition, the NF-κB pathway could be induced, and inhibition of the NF-κB pathway could alleviate the fibrosis caused by MSNs. We conclude that inflammation is a major effector of the acute kidney toxicity induced by MSNs and results in renal interstitial fibrosis, which is mediated by the NF-κB signaling pathway.Keywords: mesoporous silica nanoparticles (MSNs), acute kidney injury, renal interstitial fibrosis, NF-κB